ASSESSING THE PREVENTIVE PRACTICES OF WORKERS REGARDING OCCUPATIONAL HEALTH HAZARDS IN ENUGU STATE, NIGERIA - Ugwu, Dorothy I. (International Journal of Human Kinetics, Health and Education, 2023)
The study assessed the preventive practices regarding occupational health hazards among workers in Anambra Motor Manufacturing Company (ANAMCO), Enugu, Nigeria. The descriptive survey design was used for the study. The population for the study consisted of 521 workers of ANAMCO. The instrument used for the study was the Occupational Health Hazard Preventive Practices Questionnaire (OHHPPQ), which was designed by the researcher. The face validity of the instrument was determined through the judgement of three experts from the departments of HPE and Social Sciences in UNN. Split half reliability of .85 was obtained for the instrument. Stratified sampling technique was used to draw sample for the study. Frequency, percentages and chi-square statistics were used for data analysis. Results revealed that workers’ acceptance of protective devices depends on their belief that the devices give them minimal discomfort; when management breach the contractual agreement regarding the provision of protective measures, it dampens workers’ interest in obeying workplace regulations and finally, the junior workers differed significantly from the senior workers in their adoption of preventive practices regarding occupational health hazards. Following from these findings, it was recommended, among others, that more workshops, seminars and training should be organized for all workers, especially the senior workers in order to reduce their risk taking practices.